Cerebral Venous Sinus Thrombosis (CVST) as a Complication of SARS-COV2 Infection. Issue 1 (June 2022) - Pujari, Shripad S.; Ojha, Pawan K.; Kulkarni, Rahul V.; Kharat, Sumit; Gupta, Dulari; Lalla, Rakesh; Panchal, Keyur; Walzade, Priyanka S.; Palasdeokar, Nilesh; Nadgir, Dattatraya; Nirhale, Satish; Dhonde, Pramod; et al.
Background and Purpose: Severe acute respiratory syndrome coronavirus 2 (SARS-COV2) infection induces a prothrombotic state frequently associated with arterial ischemic strokes. Cerebral venous sinus thrombosis (CVST) is also reported with corona virus disease-19 (COVID-19) but a large cohort study is lacking. Our aim was to study the characteristics, treatment response, and outcomes of CVST occurring in association with COVID-19 (COVID-CVST) and the causal relationship with COVID-19. Methods: Data of 34 patients admitted in COVID facility and suffering from CVST and SARS-COV2 infection was studied with respect to their clinic-radiological and lab features, predisposing factors, treatment, and outcome. Observations and Results: 15 patients with CVST were detected positive for COVID but remained asymptomatic for the same. 14 patients had CVST along with symptoms of COVID, whereas 5 had CVST after recovery from COVID, at an average of 18 days after COVID-19. 4 patients were on aspirin as prophylaxis against thrombo-embolic events. The number of males exceeded females (22:12), conventional risk factors were seen in only 8 patients (postpartum state-3, alcohol abuse-2 and anemia-3), whereas the majority (26/34) showed none of them. The mean serum homocysteine level was normal and antiphospholipid antibody was tested normal in the assessed subjects. D-dimer and C reactive protein were elevated in all. 4 symptomatic patients who suffered from severe pneumonia died because of systemic complications. Conclusion: COVID-19 predisposes to CVST and the outcome is related to the severity of COVID pneumonia. CVST related to COVID occurs during or after a few weeks of COVID pneumonia and can also be seen in asymptomatic SARS-COV2 infection. COVID-19 can occur independently or in association with traditional thrombotic risk factors which increase the risk and severity of CVST in COVID. If recognized early, CVST associated with COVID can usually be treated effectively to achieve a very good outcome.